Endosialin promotes vascular maturation by inhibiting Cyr61 expression in melanoma metastasis - Lu, Tong; Song, Hongtao; Zhao, Zhite; He, Xinglin; Xu, Chao; Liu, Shaojie; Qin, Weijun; Yang, Bo; Yang, Lijun (Frontiers in Oncology, 2025)
BackgroundExtensive tumor cell metastasis is associated with poor patient prognosis. Tumor endothelial cells demonstrate distinct proangiogenic phenotypes compared to normal endothelial cells, partially mediated by pericyte-derived secreted factors. Endosialin, a pericyte biomarker implicated in vascular maturation and metastatic progression, remains mechanistically undefined in this context.MethodsB16F10 melanoma cells were injected via caudal vein into Endosialin knockout (ENKO) and wildtype mice. Lung metastases were quantified through hematoxylin-eosin (HE) staining. Vascular architecture was analyzed using Evans blue perfusion and CD31 immunofluorescence. Molecular mechanisms were investigated through western blotting, qPCR, proliferation assays, and in vitro lumen formation models.ResultsBioinformatics analysis revealed Endosialin overexpression correlates with enhanced angiogenesis and poor clinical outcomes. Endosialin deficiency significantly reduced pulmonary metastasis burden. Vascular profiling showed ENKO mice exhibited increased small-diameter vessels (<50 μm) and reduced mature vessels (≥50 μm). Mechanistically, Endosialin regulates vascular maturation through Erk1/2-mediated suppression of Cyr61 in pericytesConclusionEndosialin facilitates melanoma metastasis by promoting vascular maturation via Erk1/2-Cyr61 signaling axis in pericytes.